COVID-19: DIFFICULTIES FACED BY CHINA’S RETAILING INDUSTRY AND RECOMMENDATIONS TO OVERCOME THEM - Chao Li; Jasmine A.L. Yeap; T. Ramayah (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Since the spread of COVID-19, the world’s economy has been seriously affected with the retailing industry being one of the hardest hit industries. China is one of the earliest countries to experience the virus outbreak and economy depression in the first quarter of this year and its retailing industry has gone through many challenges which witnessed a change in consumers’ buying decisions. For this reason, it’s very necessary for marketers to think about how to respond to the changes taking place in the retailing industry and overcome their shortcomings in the new era. In this paper, we will describe the difficulties faced by the retailing industry in China and discuss some recommendations that can be undertaken by the retailers, small and big alike, to better manage their business in the time of Covid-19. The recommended measures can serve as a guide for other countries to alleviate the impact caused by the coronavirus.